Geotechnical aspects of reconnaissance findings after 2020 January 24th, M6.8 Sivrice-Elazig-Turkey earthquake - Cetin, Kemal Onder; Cakir, Elife; Ilgac, Makbule; Can, Gizem; Soylemez, Berkan; Elsaid, Alaa; Gor, Mesut (Springer, 2021)
On January 24, 2020, Sivrice-Elazig-Turkey earthquake occurred along the East Anatolian Fault Zone. The moment magnitude of the event was reported as 6.8. This paper documents reconnaissance findings performed immediately after the event. Investigated sites namely, Lake Hazar shores, Karakaya Dam Reservoir-Euphrates River shores, Malatya-Battalgazi district and its villages, and Elazig Downtown are predicted to be shaken by rock peak ground acceleration, PGA(VS30=1100 m/s), levels of 0.12-0.42 g, 0.05-0.11 g, 0.05 g, and 0.08 g respectively. The documented geotechnical field performances vary from widespread liquefaction-induced sand boils and lateral spreading, to no signs of surface manifestations of permanent ground deformations or soil liquefaction. In Battalgazi district and Elazig Downtown, the foundation performances vary from no signs of permanent ground deformations to 1-3 cm settlements, and 1-2 cm lateral movements. Additionally, the hydraulic structures inspected are estimated to be shaken by PGA(VS30=1100 m/s) levels of 0.03-0.23 g. Other than a minor longitudinal cracking along a limited section along the crest of a homogeneous earthfill dam, no apparent signs of permanent ground deformations were reported. Last but not least, a number of rock falls were mapped, based on back analyses of which probable peak ground velocities at these rockfall sites were speculated.
Keywords: Reconnaissance; Sivrice earthquake; Liquefaction; Hydraulic structures; Foundations; Seismic performance